1991
DOI: 10.1044/jshr.3401.129
|View full text |Cite
|
Sign up to set email alerts
|

The Language-Reading Relationship in Normal and Reading-Disabled Children

Abstract: In this study, the word retrieval, phonological awareness, sentence completion, and narrative discourse processing skills of 93 reading-disabled and 93 normally achieving subjects from 8 to 14 years of age were compared. The subjects were matched for age, sex, and neighborhood. Results revealed that the two groups differed significantly on the time and accuracy of word retrieval, their ability to produce a syntactically appropriate structure in a sentence completion task, their retelling of stories that had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 32 publications
4
39
2
Order By: Relevance
“…Weak story structure knowledge may limit the formation of these mental models, not only restricting children's ability to derive meaning from written text, but also constraining their ability to produce well-structured oral narratives (or stories). Older children with specific reading disability 1 are known to demonstrate difficulties in oral narrative ability (e.g., Roth & Spekman, 1986;Snyder & Downey, 1991). However, little is known about how children with specific reading disability develop oral narrative skills over time and whether the difficulties in oral narrative performance are a consequence of their limited reading experience.…”
Section: Introductionmentioning
confidence: 99%
“…Weak story structure knowledge may limit the formation of these mental models, not only restricting children's ability to derive meaning from written text, but also constraining their ability to produce well-structured oral narratives (or stories). Older children with specific reading disability 1 are known to demonstrate difficulties in oral narrative ability (e.g., Roth & Spekman, 1986;Snyder & Downey, 1991). However, little is known about how children with specific reading disability develop oral narrative skills over time and whether the difficulties in oral narrative performance are a consequence of their limited reading experience.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that naming speed, in relation to reading, is independent of phonological awareness [48]. Snyder and Downey [73] are among those who consider that word retrieval problems, evidenced in difficulty in rapidly naming picture stimuli, are specifically evident in reading-disabled children between 7 and 12 years of age.…”
Section: Word Findingmentioning
confidence: 99%
“…Catts and Kamhi [1] consider that naming deficits may arise from difficulties in retrieving phonological codes from long-term memory, a view also expressed by Snyder and Downey [73]. Referring to intervention, Catts [19] states that studies have yet to show that word retrieval intervention can significantly influence reading achievement, thus contrasting with the known effects of phonological awareness intervention.…”
Section: Word Findingmentioning
confidence: 99%
“…Second, there is a strong relationship between oral language competence and reading in typically developing and in non-autistic language-impaired populations. Aspects of oral language ability, including, phonology, syntax, narrative ability, metalinguistic awareness, and vocabulary have been shown to be critical predictors of reading acquisition and literacy achievement (Catts, Fey, Zhang, & Tomblin, 1999;Nation, Clarke, Marshall & Durand, 2004;Roth, Speece, Cooper, De La Paz, 1996;Snyder & Downey, 1991). Therefore, it is seems likely that children with HFA will demonstrate significant variability in literacy as well as reported variability in oral language and communication.…”
mentioning
confidence: 99%